Analisa Tikungan Terhadap Keselamatan Pengguna Jalan Raya Bandar Baru – Berastagi ( Kabupaten Deliserdang – Kabupaten Karo ) - Budi Florianta Tarigan, S.T., M.T.; Seno Imanuel Sitepu, S.T (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2019)
Basically the construction of a highway is the process of opening a traffic room that overcomes various geographical obstacles. In road design, the geometry of the road must be set in such a way that the road in question can provide optimal service to traffic according to its function. Roads that are used as locations are several roads located in the area of North Sumatra, Deli Serdang Regency and Karo Regency, namely Three (3) STAs, such as (STA 49 + 400 Bend Amoy I), (STA 50 + 500 Bend Amoy II), ( STA 58 + 300 Pelawi Bend). Data identification results, STA 49 + 400 Amoy I bend using spiral-spiral (SS) type, STA STA 50 + 500 Amoy II bend using spiral-spiral (SS) bend type, and STA 58 + 300 Pelawi bend using spiral bend type -spiral (SS) too. Therefore all three points of the STA must get special treatment to reduce the possibility of an accident.